The Sacred Myths at Gunung Bawakaraeng Post Three: Roland Barthes' Semiotic Studies - Rahmat Sulo; Lukman Lukman; Ery Iswary (Hasanuddin University, 2023)
The aims of this research are (1) to describe the forms of sacred myths at Gunung Bawakaraeng post three (2) to describe the influence of sacred myths at three Bawakaraeng posts on the local community and climbers. The benefits of this research are (1) obtaining a description of the sacred myths at post three of Gunung Bawakaraeng and (2) the availability of forms of influence of sacred myths at post three of Gunung Bawakaraeng. This research used qualitative method. The results of this research indicate that (1) there are forms of sacred myths at post three of Gunung Bawakaraeng, such as: (a) the story of the Dutch lady (Noni) who roams around the big tree at post three, (b) the occult market or also commonly known as Pasar Anjaya, c) there are cases of climbers getting lost, (d) there is a pilgrimage ritual; and (2) there is the influence of sacred myths at post three of Gunung Bawakaraeng, such as: a group of people (climbers and the local community) built a belief about (a) the story of a Dutch lady who wanders around the big tree at post three, (b) a magical market or also commonly referred to as anjaya market, c) there is a case of climbers getting lost, (d) there is a pilgrimage ritual.